Onwards and upwards: why companies change their executive remuneration schemes, and why this leads to increases in pay - Bender, Ruth (Blackwell Publishing Ltd, 2006)
Much has been written about the phenomenon of ever-increasing executive pay in listed companies. This paper examines some of the underlying reasons for this continued increase in executive directors’ remuneration. It reports the results of 40 interviews with protagonists in the remuneration debate in FTSE 350 companies, exploring the types of change made and the reasons given for these changes. This issue has not specifically been addressed by previous studies. Reasons given for making changes included: increases due to being below market; changing performance-related schemes that did not pay out or paid less than the anticipated amount; changes in the company's culture or strategy; changes to senior personnel (executive and non-executive); compliance with good human resources practice; and a perceived need to comply with best practice in corporate governance. The results are analysed through two theoretical lenses. An agency theory explanation provides insight into the structure of executive remuneration contracts, and expectancy theory suggests why schemes might be changed to motivate the executives. The expectancy theory explanation tempers the agency theory explanation, showing why changes are made even though this may lead to moral hazar
Keywords: Executive remuneration; Agency theory; Performance-related pay